Pendampingan Peningkatan Kualitas Praktik Pengalaman Lapangan (PPL) PAI Melalui Evaluasi Model CIPP Di MA Plus Al Amanah Sawangan - Handayani, Fitri; Sumiati, Yuyum; Hestiningrum, Mayang Jelita; Salsabila, Dinda; Rizqi, Shakilla; Ridho, Afuan; Fahrizal, Refi; Maulana, Sahrul (At Taawun Bangun Bangsa, 2025)
The Field Experience Program (PPL) is an integral component in preparing prospective Islamic Religious Education (PAI) teachers. This community service activity aims to assist and evaluate the implementation of the PPL at Madrasah Aliyah (MA) Plus Al-Amanah Sawangan using the CIPP (Context, Input, Process, Product) model as a framework for generating improvement recommendations. A collaborative participatory approach was employed to ensure active involvement of all stakeholders at every stage. The activities included workshops, intensive mentoring, observations, and focused discussions. The evaluation results indicate that: (1) the context aspect shows strong alignment between PPL objectives and the needs of the madrasah; (2) the input aspect reveals that students are generally well-prepared, although enhancement in digital learning innovation is needed; (3) the process aspect runs effectively despite challenges in coordination and time management; and (4) the product aspect demonstrates improvement in students’ pedagogical and professional competencies. This program resulted in strategic recommendations to improve future PPL implementation, particularly in strengthening collaboration and technology integration.